2018
DOI: 10.1187/cbe.17-10-0225
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Analytical Framework to Characterize Student Reasoning about Complex Processes

Abstract: Real-world processes are complex and require ideas from multiple disciplines to be explained. However, many science courses offer limited opportunities for students to synthesize scientific ideas into coherent explanations. In this study, we investigated how students constructed causal explanations of complex phenomena to better understand the ways they approach this practice. We interviewed 12 undergraduate science majors and asked them to explain real-world phenomena. From these interviews, we developed a ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 50 publications
(93 reference statements)
0
17
0
1
Order By: Relevance
“…The need for materials that help students make connections both between science courses and with other related disciplines has been recognized by students and instructors alike 4–8 . As a way to provide these opportunities, both researchers and practitioners have set out to develop assessments, 9,10 lessons, 6,11,12 tutorials, 13 and even whole courses 14–16 meant to help students integrate multiple disciplines such as chemistry, biology, physics, and mathematics 17 . Implementations of some of these materials have suggested that students who are exposed to multidisciplinary experiences exhibit a positive attitude and develop a greater interest in science than students who are not 9,13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for materials that help students make connections both between science courses and with other related disciplines has been recognized by students and instructors alike 4–8 . As a way to provide these opportunities, both researchers and practitioners have set out to develop assessments, 9,10 lessons, 6,11,12 tutorials, 13 and even whole courses 14–16 meant to help students integrate multiple disciplines such as chemistry, biology, physics, and mathematics 17 . Implementations of some of these materials have suggested that students who are exposed to multidisciplinary experiences exhibit a positive attitude and develop a greater interest in science than students who are not 9,13 …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] As a way to provide these opportunities, both researchers and practitioners have set out to develop assessments, 9,10 lessons, 6,11,12 tutorials, 13 and even whole courses [14][15][16] meant to help students integrate multiple disciplines such as chemistry, biology, physics, and mathematics. 17 Implementations of some of these materials have suggested that students who are exposed to multidisciplinary experiences exhibit a positive attitude and develop a greater interest in science than students who are not. 9,13 Furthermore, in recent years, considerable efforts have been made by researchers, practitioners, and leaders in science education toward the development of assessment tasks that reflect the vision proposed by the National Research Council's Framework for K-12 Science Education (the Framework).…”
Section: Introductionmentioning
confidence: 99%
“…This can be done using products produced by students (e.g., homework, lab reports), attitudinal gains measured with surveys, participation rates in activities, interview testimonials, classroom discourse practices, and formative assessment or exam data (e.g., Reiser et al, 2001;Cobb et al, 2003;Barab and Squire, 2004;Mohan et al, 2009). Regardless of the source, evidence must be in a form that supports a systematic analysis reasoning was embodied in our instructional approach by being the central focus of all instructional materials, which included: a revised version of the Flux Reasoning Tool ( Figure 2); case study-based units in lecture that explicitly emphasized flux phenomena in real-world contexts (Windschitl et al, 2012;Scott et al, 2018; Figure 3); classroom activities in which students practiced using flux to address physiological scenarios; links to online videos describing key flux-related concepts; constructed-response assessment items that cued students to use flux reasoning in their thinking; and pretest/ posttest formative assessment questions that tracked student learning (Figure 4).…”
Section: Phase 3: Evaluating the Instructional Toolsmentioning
confidence: 99%
“…In our work, the theoretical claim that instruction based on fundamental scientific concepts would support students’ flux reasoning was embodied in our instructional approach by being the central focus of all instructional materials, which included: a revised version of the Flux Reasoning Tool ( Figure 2 ); case study–based units in lecture that explicitly emphasized flux phenomena in real-world contexts ( Windschitl et al. , 2012 ; Scott et al. , 2018 ; Figure 3 ); classroom activities in which students practiced using flux to address physiological scenarios; links to online videos describing key flux-related concepts; constructed-response assessment items that cued students to use flux reasoning in their thinking; and pretest/posttest formative assessment questions that tracked student learning ( Figure 4 ).…”
Section: Design-based Research In Action: An Example From Undergraduate Physiologymentioning
confidence: 99%
“…In particular, causal reasoning is one of the most basic cognitive processes that enable conceptual understandings and problem solving (Jonassen and Ionas 2008). When contemplating real-world phenomena, students often struggle to identify and apply relevant patterns to explain the underlying system's mechanisms (Andersson, Löfgren, and Tibell 2020;Düsing, Asshoff, and Hammann 2019;Eilam and Reisfeld 2017;Scott et al 2018). The reason might be that it is difficult for them to recognise relevant scientific concepts.…”
Section: Challenges To Feedback Loop Reasoningmentioning
confidence: 99%